From Bad Faith to Authenticity: A Sartrean Reading of Living (2022) - Pirmansyah Pirmansyah; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This study examines the transformation of the character Mr. Williams in Oliver Hermanus' film Living (2022) through Jean-Paul Sartre's philosophy of existentialism, focusing on how his behavior before being convicted of illness reflects the concept of Bad Faith and how his terminal illness leads him to Authenticity. This descriptive qualitative research makes dialogues, actions, and narrative events in film as data, which is analyzed through the Interactive Model of Miles, Huberman, and Saldaña (2014) with the stages of reduction, presentation, and drawing data conclusions. The results of the study showed that Bad Faith Williams before being sentenced was a coordinated condition at the personal, institutional, and domestic levels, as seen through her office routine, handling citizen petitions, renaming her condition by a colleague, and her household silence. His journey to Authenticity is then revealed through five stages: a diagnosis that erases the illusion of infinite time, a failed escape that results in an unfinished act of self-expression, the disclosure of his condition to someone outside of his or her social role, an ongoing civic project, and a death that completes a once-delayed self-expression. The discussion places these findings in Sartre's concept of seriality as well as previous research, arguing that Williams's Bad Faith is structural, while its authenticity is determined by the ownership of freely taken choices, not by the direction of those choices.